Radiation sterilization of ephedrine in the solid state - Dettlaff, Katarzyna; Teżyk, Artur; Marciniec, Barbara; Wachowiak, Roman; Naskrent, Marek; Bednarek, Bartłomiej (Polish Chemical Society and the Committee on Analytical Chemistry of Polish Academy of Sciences with cooperation of the Czech Chemical Society, the Slovak Chemical Society and the Hungarian Chemical Society, 2008)
The effects of the e-beam ionising radiation of energy 9.96 MeV in doses 25 800 kGy on the stability of solid ephedrine hydrochloride (1R,2S)-(-)-2-methylamino-1-phenyl-1-propanol hydrochloride) have been studied. These effects have been observed using the following analytical methods: organoleptic (form, colour, smell, clarity of solution), scanning electron microscope SEM, pH measurement, chirality and water content measurement (Karl Fischer method), spectrometric methods (UV, FT IR, EPR), chromatography (TLC), and combined chromatography (TLC UV, GC MS). Even the standard sterilisation dose of 25 kGy has been found to cause a change in colour from white to pale yellow, the appearance of free radicals in the concentration of 3.05×10^15 spin/g, and about 1% loss of the content. The effects of higher doses 50 800 kGy have shown that radiodegradation degree of the compound is proportional to the dose applied. The main product of radiodegradation, formed at a yield of G = 17.17×10^7 mol/J, has been identified as 2-methylamino-1 phenyl-1-propanone (methcathinone, ephedrone), a psychoactive compound of the activity similar to that of amphetamine. For the above reasons ephedrine hydrochloride can not be subjected to radiative sterilisation with a dose of 25 kGy, however, assuming sufficiently low microbiological contamination of the initial substance, lower doses could be probably used for sterilisation purposes. Our results have not confirmed the earlier reports from 1970s on the resistance of ephedrine to ionising radiation in doses up to 60 kGy.
Keywords: Ionising radiation; Drug sterilization; Ephedrine hydrochloride; Product of radiolysis; methcathinone